rpm 2020
DOI: 10.21926/rpm.2002013
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene Topography Sticker Array for Cell-Based Assays

Abstract: Cells can respond to different topographical cues in their natural microenvironment. Hence, scientists have employed microfabrication techniques and materials to generate culture substrates containing topographies for cell-based assays. However, one of the limitations of custom topographical platforms is the lack of adoption by the broad research community. These techniques and materials have high costs, require high technical expertise, and can leach components that may introduce artifacts. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…To investigate the effect of surface microtopography on cell behavior, we first fabricated PS sticker-like topographies with three different levels of roughness generated by microscopic linear scratches characterized by their average surface roughness (Ra). In addition, geometrical micropatterns (depicted by spiral and zigzags) and grooves were generated on the PS using razor printing and polishing methods ( Figure 1A ), as described previously ( Rosado-Galindo and Domenech, 2020 ). Human TNBC cell lines, MDA-MB-231 and MDA-MB-468, were cultured on topographical surfaces, and viability, morphology, and proliferation were measured as initial indicators of potential phenotypic changes in the cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the effect of surface microtopography on cell behavior, we first fabricated PS sticker-like topographies with three different levels of roughness generated by microscopic linear scratches characterized by their average surface roughness (Ra). In addition, geometrical micropatterns (depicted by spiral and zigzags) and grooves were generated on the PS using razor printing and polishing methods ( Figure 1A ), as described previously ( Rosado-Galindo and Domenech, 2020 ). Human TNBC cell lines, MDA-MB-231 and MDA-MB-468, were cultured on topographical surfaces, and viability, morphology, and proliferation were measured as initial indicators of potential phenotypic changes in the cells.…”
Section: Resultsmentioning
confidence: 99%
“…The topographies evaluated in this study were the surface roughness, grooves, and curvature geometries generated on flat polystyrene (PS) films, as described in our previous work ( Stallcop et al, 2018 ; Rosado-Galindo and Domenech, 2020 ). Briefly, a biaxially oriented, 0.19 mm thick PS film (ST311190/3, Goodfellow) and medical-grade tape (ARCare 90106) were used to produce the topographical surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…The topographical polystyrene-based (PS-based) array was developed using razor printing, oxygen plasma and sanding methods as described in our previous works (Additional file 1 : Figure S1) [ 29 , 37 ]. Topographies examined were roughness, curvature and wettability on flat PS films.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, studies on the effect of spacing, orientation and diameter of micropore/nanorod patterned surfaces proved that straight patterns with relatively low spacing were more effective on MSCs proliferation and differentiation to osteogenic lineage for improved clinical performance of bone implants [ 28 ]. Our previous studies also demonstrated that polystyrene substrates with increased level of roughness enhanced the proliferation of adipose-derived MSCs and the expression of factors associated with proliferation, and thus, this physical stimulation could minimize the need for biochemical supplementation in cultures [ 29 ]. Likewise, surface topography has been shown to influence the behavior of other types of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Methods such as image segmentation allow the identification of structures with specific characteristics [ 25 , 26 ]. To accommodate the blood sample to be processed, simple microfluidic configurations are often used, offering several advantages [ 27 , 28 , 29 , 30 ]. Other techniques, such piezocoagulography, have been also utilized for blood coagulation, showing also the possibility of studying the initial stage of fibrin formation in the clotting process [ 31 ].…”
Section: Introductionmentioning
confidence: 99%